2008
DOI: 10.1177/1076029608325546
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Leiden Mutation and Thrombotic Occlusion of Microsurgical Anastomosis After Free TRAM Flap

Abstract: The transverse rectus abdominis muscle flap is widely used in free microvascular tissue transfer for breast reconstruction following mastectomy. Flap survival may be compromised by failure at the microsurgical anastomosis due to both venous and arterial thrombosis. It is unclear, whether hereditary thrombophilia represents a risk factor for early thrombotic occlusion following free flap procedures. We present a case of a patient with previously diagnosed activated protein C resistance caused by heterozygous fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 12 publications
(20 reference statements)
0
26
0
Order By: Relevance
“…[83][84][85][86][87][88][89][90][91][92][93] In a recent article by Wang et al examining 58 free flaps in patients with a variety of procoagulant states including factor V Leiden mutation, protein C deficiency, hyperhomocysteinemia, antiphospholipid antibody syndrome, prothrombin gene mutation, factor VIII elevation, anticardiolipin antibody syndrome, and essential thrombocytosis, a 20 percent rate of thrombosis and a 0 percent rate of salvage in flaps that had clotted postoperatively was reported (Level IV Evidence). 94 A retrospective series of 2260 free flaps concluded that elevated platelet count (>300,000/μl) and thrombophilia were risk factors for failure of a take-back, suggesting that platelet-derived blood coagulation pathways are important contributors to the flap failure pathologic condition (Level III Evidence).…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…[83][84][85][86][87][88][89][90][91][92][93] In a recent article by Wang et al examining 58 free flaps in patients with a variety of procoagulant states including factor V Leiden mutation, protein C deficiency, hyperhomocysteinemia, antiphospholipid antibody syndrome, prothrombin gene mutation, factor VIII elevation, anticardiolipin antibody syndrome, and essential thrombocytosis, a 20 percent rate of thrombosis and a 0 percent rate of salvage in flaps that had clotted postoperatively was reported (Level IV Evidence). 94 A retrospective series of 2260 free flaps concluded that elevated platelet count (>300,000/μl) and thrombophilia were risk factors for failure of a take-back, suggesting that platelet-derived blood coagulation pathways are important contributors to the flap failure pathologic condition (Level III Evidence).…”
Section: Peripheral Vascular Diseasementioning
confidence: 99%
“…Previous studies have reported undiagnosed hypercoagulability as a cause for unpredictable flap failures. [6][7][8][9][10][11] It was quite surprising to see that the incidence of hypercoagulability was not at all low, which goes to show that the state of hypercoagulation may be considered an underestimated condition. The percentages of newly diagnosed hypercoagulation shown in this study display the importance of questioning risk factors and testing accordingly for hypercoagulation in patients seeking microsurgical breast reconstruction.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al [5] retrospectively analyzed all patients with hypercoagulability diagnoses as well as patients with prior thrombotic events who underwent free tissue transfer and found an alarming 15.5% rate of flap loss in these patients. Several other authors have shown a high rate of complications in patients with FVL after DIEP flap reconstruction [2, 68]. There are no similar reports in the literature of DIEP flap reconstruction on patients with established FVL without postoperative complications—neither systemic, nor localized to the surgical site.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients received 3000 units of UFH intraoperatively based on borderline high preoperative TEG values (Table 1). In contrast, Handschin et al [8] did not begin UFH administration until noticing an ischemic flap when the arterial anastomosis was already thrombosed. Khansa et al [6] did not use any intravenous UFH in their two cases of FVL and flap failure.…”
Section: Discussionmentioning
confidence: 99%